Socioeconomic profile and symptoms associated with the use of non-traditional smoking devices in the state of São Paulo-Brazil (Revista Contexto & Saúde, 2025)
Introduction: The use of electronic smoking devices (ESDs) exposes the body to chemical components contained in the vapor. These include carcinogens and cytotoxic substances, potentially associated with lung and cardiovascular diseases. In regular hookah users, it is possible to observe elevated levels of carbon monoxide (CO) and carboxyhemoglobin (COHb), both for sessions that use tobacco and nicotine, and for sessions free of these components. Objective: To analyze the behavior of young people in the state of São Paulo regarding the use of hookah and ESDs. To verify the frequency of use of these devices, the knowledge of young people about the physiological effects of using these devices and the consequences for health. Method: This is a prospective observational study in which a questionnaire was applied to collect information about the use of hookah and ESDs among young people in the state of São Paulo. Conclusion: The habit of smoking these devices is frequent and is already present in the daily lives of people, especially young people, as a form of social interaction. Even though they are aware of the health risks posed by these devices and have already experienced some adverse effects during and/or after a smoking session, users continue to use them. This reinforces the need for public health policy campaigns emphasizing the consequences of exposure to smoke from electronic cigarettes and hookahs.